Experimental evaluation of avalanche type of electron heat transport in magnetic confinement plasmas. (1st January 2023) - Kin, F.; Itoh, K.; Bando, T.; Shinohara, K.; Oyama, N.; Yoshida, M.; Kamiya, K.; Sumida, S.
Abstract: Turbulent transport is undoubtedly important in magnetic confinement plasmas. It has been reported that a lot of transport dynamics are not satisfying the local diffusive models. Here, we report the quantitative measurement of electron heat flux associated with ballistic propagating long-range transport events, which is considered to be a component of avalanches. In addition, we show the first observations of the substantial impact of avalanche-driven transport on profile resilience (or profile stiffness) observed in JT-60U. We found that, in the channel of the electron heat flux, the ratio between the increment of the avalanche-driven component to that of the total plasma heating becomes dominant (∼80%) in the case of the high-heating limit. This suggests a possible role for avalanche-driven transport to induce profile resilience, which has been evidenced by flux-driven simulations.